The problem of plasma density increasing in the U-3M torsatron after RF heating termination - Pashnev, V.K.; Tarasov, I.K.; Sitnikov, D.A.; Bondarenko, V.N.; Chechkin, V.V.; Shapoval, A.N.; Pavlichenko, R.O.; Tarasov, M.I.; Sorokovoy, E.L.; Petrushenya, A.A.; Skibenko, A.I.; Karpuhin, L.L.; et al. (Вопросы атомной науки и техники, 2013)
In the U-3M torsatron a significant chord-averaged plasma density increase is observed after the RF-heating termination. The objective of this work is to find out possible mechanisms resulting in plasma density increasing. В торсатроне У-3М можно увидеть значительное увеличение средней плотности плазмы после прекращения ВЧ-нагрева. Целью данной работы является выяснение механизмов, приводящих к такому увеличению. У торсатроні У-3М можна побачити значне збільшення середньої густини плазми після припинення ВЧ-нагрівання. Метою даної роботи є з'ясування механізмів, що призводять до такого збільшення.